2016
DOI: 10.1007/s11606-016-3701-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Intimate Partner Violence among Women Veterans who Utilize Veterans Health Administration Primary Care

Abstract: OBJECTIVES:The objectives of this study were to identify the prevalence of past-year intimate partner violence (IPV) among women Veterans utilizing Veterans Health Administration (VHA) primary care, and to document associated demographic, military, and primary care characteristics. DESIGN: This was a retrospective cohort design, where participants completed a telephone survey in 2012 (84% participation rate); responses were linked to VHA administrative data for utilization in the year prior to the survey. PART… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
75
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 94 publications
(81 citation statements)
references
References 37 publications
6
75
0
Order By: Relevance
“…Although the majority of women in our study (56%) reported a history of MST, MST was not associated with risky sexual behavior in the final model. This was a surprising finding given other research that associates MST with other interpersonal trauma correlates like childhood sexual abuse (Wilson, Kimbrel, Meyer, Young, & Morissettea, 2015) and IPV (Kimerling et al, 2016). An evaluation based on disaggregated MST questions (sexual assault vs. sexual harassment) would shed further light on the association noted here.…”
Section: Discussionsupporting
confidence: 51%
“…Although the majority of women in our study (56%) reported a history of MST, MST was not associated with risky sexual behavior in the final model. This was a surprising finding given other research that associates MST with other interpersonal trauma correlates like childhood sexual abuse (Wilson, Kimbrel, Meyer, Young, & Morissettea, 2015) and IPV (Kimerling et al, 2016). An evaluation based on disaggregated MST questions (sexual assault vs. sexual harassment) would shed further light on the association noted here.…”
Section: Discussionsupporting
confidence: 51%
“…10 A telephone survey study of a nationally representative sample of women veterans receiving primary care in VHA found declining rates of past-year IPV with age, but substantial proportions of women reported IPV in middle and older age. 14 These prior studies of older women have been limited to assessing IPV prevalence via survey methodology, which may result in greater disclosure than through clinical screening.…”
Section: Introductionmentioning
confidence: 99%
“…When compared to women without military experience, women who have served in the military have reported higher rates of lifetime IPV (measured as threatened or actual physical violence, or unwanted sex, from a current or former intimate partner; Dichter, Cerulli, & Bossarte, 2011). In survey research, nearly 1 in 5 women veterans receiving primary care from the Veterans Health Administration (VHA) reported past-year IPV, with higher rates (1 in 4) among women up to age 30 (Kimerling et al, 2016). Among women screened for IPV as part of their clinical care within the VHA, 8.7% had a documented positive screen for past-year IPV (Dichter, Haywood, Butler, Bellamy, & Iverson, 2017).…”
mentioning
confidence: 99%